2016
DOI: 10.1002/smj.2570
|View full text |Cite
|
Sign up to set email alerts
|

The impact of context and model choice on the determinants of strategic alliance formation: Evidence from a staged replication study

Abstract: Research summary: Endogenous characteristics of alliance network structure have repeatedly been shown to predict future alliance ties in the strategic management literature. Specifically, the concepts and measures of relational, structural, and positional embeddedness (per Gulati and Gargiulo, 1999), as well as interdependence, are foundational for many studies. We explore these determinants of alliance formation by replicating the baseline analyses of Ahuja, Polidoro, and Mitchell's, 2009 SMJ article. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…These meta-analytical findings therefore confirm our initial idea of the complementarity of embeddedness and proximity (also acknowledged in recent research, e.g. Ghosh et al (2016);Mindruta, Moeen, and Agarwal (2016)). It shows that a parsimonious theory of tie formation needs to consider both.…”
Section: Summary and Theoretical Interpretationsupporting
confidence: 78%
See 1 more Smart Citation
“…These meta-analytical findings therefore confirm our initial idea of the complementarity of embeddedness and proximity (also acknowledged in recent research, e.g. Ghosh et al (2016);Mindruta, Moeen, and Agarwal (2016)). It shows that a parsimonious theory of tie formation needs to consider both.…”
Section: Summary and Theoretical Interpretationsupporting
confidence: 78%
“…Ghosh, Ranganathan, and Rosenkopf (2016), for instance, replicated the study of Ahuja, Polidoro, and Mitchell (2009), but observed an opposite relational embeddedness effect. With respect to structural and positional embeddedness, Rosenkopf and Padula (2008) state that: "In contrast to extant studies, however, our results show that [structural embeddedness] has no significant effect on new alliance formation among firms residing in different clusters [and] neither [positional embeddedness] nor [status similarity] affects alliance formation within clusters" (p. 680).…”
Section: Introductionsupporting
confidence: 69%
“…Our research aim was to use the data that was collected from organizations in Asian countries, using de Waal's HPO Framework, to identify the main organizational areas which have to be strengthened in order for 'the typical Asian organization' to be able to transform into an HPO. We realize there is no such thing as 'a typical Asian organization' but it is possible to group organizations according to their regional location into a more or less homogeneous group for research purposes, as researchers have done before us (for instance Ghosh et al, 2016;Hofstede, 1980;Kloudova and Stehlikova, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, centrality, structural hole, and closeness centrality are three typical positional attributes. Ghosh et al (2016) used combined centrality to simulate positional embeddedness [15]. The extent of positional embeddedness can be measured by three indicators, which are degree centrality, betweenness centrality, and closeness centrality [25][26][27], in order to analyze the impact of each positional attribute on the resource integrating mechanism.…”
Section: The Concept and Dimension Of Positional Embeddedness (Pe)mentioning
confidence: 99%